2008
DOI: 10.1260/026361708787548792
|View full text |Cite
|
Sign up to set email alerts
|

Super-Energy-Saving Dewatering Method for High-Specific-Surface-Area Fuels by Using Dimethyl Ether

Abstract: There is a growing need for the economical dewatering of highspecific-surface-area fuels containing large amounts of water, such as coal and sewage sludge. The principle underlying conventional dewatering methods is evaporation of the water content by heating the fuels to a high temperature, but this approach consumes a considerable amount of energy. The Central Research Institute of the Electric Power Industry (CRIEPI) has developed a method for the extraction of this water through the use of dimethyl ether (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Based on the characteristics of DME mentioned above, Kanda reported that liquefied DME can be used as a solvent to extract water from high-water content solids [23,24],including low rank coals [23,[25][26][27], plants, foods [24,28], sewage sludge [29], and polymers [30]. Similarly, Catchpole et al reported the extraction of pungent components from low-water content chili, black pepper, and ginger by liquefied DME [31].Sato and Matsumura reported extraction of phenol in water phase by liquefied DME [32].Thereafter, Kanda [33] and Catchpole et al [34] applied the water extraction method for the extraction of oily substances fromhigh-water content solids.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the characteristics of DME mentioned above, Kanda reported that liquefied DME can be used as a solvent to extract water from high-water content solids [23,24],including low rank coals [23,[25][26][27], plants, foods [24,28], sewage sludge [29], and polymers [30]. Similarly, Catchpole et al reported the extraction of pungent components from low-water content chili, black pepper, and ginger by liquefied DME [31].Sato and Matsumura reported extraction of phenol in water phase by liquefied DME [32].Thereafter, Kanda [33] and Catchpole et al [34] applied the water extraction method for the extraction of oily substances fromhigh-water content solids.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we performed a bench-scale experiment developed previously for removing water or oil from several materials. The configuration of this experiment has been described in previous papers (Kanda, 2008;Kanda and Makino, 2009;Kanda et al, 2010). Theoretically, the energy required for dewatering 1 kg of water by this method is 1109 kJ/kg water .…”
Section: Methodsmentioning
confidence: 99%
“…Features of the sludge that underwent DME dewatering to form the dewatered sludge cake were evaluated: volatile total solid (VTS) content and CHN and other metal content were measured. VTS, fixed total solid (FTS) content, and CHN content were analyzed using Japan Industrial Standard predetermined methods (Japan Industrial Standard, 1992, 1997, 2008. Other metal contents were measured by ICP-AES.…”
Section: Figure 2 Schema Of Dme Flow-type Experimental Apparatusmentioning
confidence: 99%